KARAKTERISASI PRODUK PENGECORAN MANUAL HIGH PRESSURE DIE CASTING PADA MATERIAL ADC 12 - Paryono Paryono; Lorentius Yosef Sutadi; Edy Suwarto (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Small and medium industries in the field of metal casting have a challenge is how to be able to produce castings that meet the standards, because usually IKM  produces art  items that  are  not bound to standards. This  situation makes IKM difficult to shift towards technical goods products due to limited knowledge and technology in this casting field. The method commonly used by the small casting industry is gravity casting with sand molds and metal molds,  but  the  results  have  not  met  the  quality  standards  required  by technical goods such as automotive parts, so one solution is to use a new method, namely High Pressure Die Casting (HPDC) which can be operated manually, this method is chosen because small industries will have difficulty in procuring this machine, so in this study a manual HPDC design is injected manually (by hand). (The material used is ADC12 where this material is suitable for the raw material of vehicle components and the mate is suitable for casting with metal molds (Die casting). The variables used in this study are mold temperature (150 0C, 1750C, and 2000C), while Cast temperature is fixed 7000C. The quality of castings products can be known from physical properties and mechanical properties by carrying out material characterization, namely: hardness test, density test and porosity test.Testing is carried out on casting specimens and obtained testing data on ADC12 casting products HPDC Manual, which is an average density of 2,744 gr / cm3, porosity on average 11.8%, average hardness 55,33 HRB. Key words: manual HPDC, ADC 12, porosity, density